2008
DOI: 10.1159/000129632
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Cell Therapy Alters LV Remodeling and Cytokine Expression but does not Improve Heart Function after Myocardial Infarction in Rats

Abstract: Objective: In this study the ability of unrestricted somatic stem cells (USSC) and mononuclear cord blood cells (MN-CBC) was tested to improve heart function and left ventricular (LV) remodeling after myocardial infarction (MI). Methods: The cells were delivered by i.v. or intramyocardial injections in rat models of MI by permanent coronary artery occlusion and by ischemia/reperfusion (I/R) injury. Heart function and remodeling was followed by recurrent echocardiography over 8 or 12 weeks after which catheteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
8
1
Order By: Relevance
“…Unexpectedly, the current study showed that at least in this animal model, USSC not only did not protect against kidney failure, but also significantly worsened it. This finding is similar to two previous studies that have shown USSC transplantation in rat and swine animal models of myocardial ischemia does not improve heart function [32,33]. In contrast to our data, Morigi et al [34] have recently shown that intravenous infusion of human umbilical cord blood MSC in immunodeficient mice with cisplatin-induced kidney injury is protective in terms of survival, renal function and histopathologic measures.…”
Section: Discussionsupporting
confidence: 92%
“…Unexpectedly, the current study showed that at least in this animal model, USSC not only did not protect against kidney failure, but also significantly worsened it. This finding is similar to two previous studies that have shown USSC transplantation in rat and swine animal models of myocardial ischemia does not improve heart function [32,33]. In contrast to our data, Morigi et al [34] have recently shown that intravenous infusion of human umbilical cord blood MSC in immunodeficient mice with cisplatin-induced kidney injury is protective in terms of survival, renal function and histopathologic measures.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have indicated the feasibility of MSCs derived from extraembryonic tissues [11], including UCB cells for the repair of ischemic heart diseases [12,13,14]. However, there are conflicting data in the literature regarding the use of UCB cells for the repair of ischemic myocardium in different animal models [15,16]. Several studies have evaluated the effects of UCBs on MI animal models.…”
Section: Introductionmentioning
confidence: 99%
“…USSC have been shown to enable reconstitution of femoral defects in mice 3,5,52 and to improve heart function after myocardial infarctions. 3,7,53,54 In this study, mesodermal differentiation capacity of the clones was confirmed by the ability of the cells to mineralize after culturing in medium that induces stem cells down the osteogenic differentiation pathway. Distinct clusters of Alizarin Red S-stained cells were observed in both clones confirming successful mineralization.…”
Section: Discussionmentioning
confidence: 68%